2016
DOI: 10.1002/ejic.201600683
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Magnetic Diversity in the Behaviour of the CuII‐bdc‐bpa System: 1D, 2D and Interpenetrated 3D Frameworks

Abstract: Metal organic frameworks (MOFs) are crystalline materials based on connections between metal ions through organic ligands. The combination of polycarboxylate anions and dipyridyl ligands is an effective strategy for producing extended structures. In this sense, the combination of bpa with m‐bdc [bpa = 1,2‐bis(4‐pyridyl)ethane, m‐bdc = 1,3‐benzenedicarboxylate] has produced three new CuII‐based networks with different dimensionalities, namely the 1D [Cu(m‐bdc)(bpa)0.5(H2O)dmf]·0.5H2O (1, synthesis based on soni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…In a previous publication [39], some of us explored the effect of selecting different non-conventional synthetic methods for the reaction between bpa and benzenedicarboxylate ( m-bdc ). In the course of these studies, microwave-assisted synthesis was found to be the most efficient method for the prepration of frameworks with higher dimensionality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous publication [39], some of us explored the effect of selecting different non-conventional synthetic methods for the reaction between bpa and benzenedicarboxylate ( m-bdc ). In the course of these studies, microwave-assisted synthesis was found to be the most efficient method for the prepration of frameworks with higher dimensionality.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, we have explored non-conventional synthetic methods for the preparation of supramolecular coordination networks that display interesting thermostructural behavior. Previous research indicated the correlation between the synthetic procedures (microwaved-assisted synthesis vs. sonochemistry) employed and the final dimensionality of the network in copper(II) coordination frameworks containing 1,3-benzenedicarboxylic acid and 1,2-bis(4-pyridyl)ethane ( bpa ) ligands [39]. Additional studies on the reversible thermal dehydration of the 1,2,4,5-benzenetetracarboxylic acid ( H 4 btec ) in the ionic [Cu(H 2 dpmd) 2 ][H 2 btec] (H 2 dpmd = dipyridilmethanediol) framework afforded drastic structural changes with associated solvatochromism.…”
Section: Introductionmentioning
confidence: 99%